2001
DOI: 10.1159/000056332
|View full text |Cite
|
Sign up to set email alerts
|

Do Shake Lotions, Zinc Oil and Polyethylene Glycol Gels Produce Dehydration or Moisturization?

Abstract: We carried out three studies to evaluate the effects of white zinc shake lotion (Zinkschüttelmixtur DAC), zinc oil ( Zinköl NRF 11.20), Lotio Cordes®, PEG ointment (Polyethylenglykolsalbe DAB) and PEG paste on nonmoisturized and moisturized skin. The aim of the study was a clear indication for these vehicles in the clinical practice. Studies 1 and 2 were performed on 20 healthy volunteers. Study 1 was carried out on nonmoisturized skin, while test areas in study 2 were treated with the study product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
2
0
2
Order By: Relevance
“…The present study has confirmed that Polyethylenglykolsalbe DAB hydrates the skin (8), as well as demonstrating that, like glycerol and urea (1–7), it improves stratum corneum barrier function.The present study cannot resolve the controversial issue of the relationship between TEWL and barrier regeneration (1, 3). However, if TEWL does control barrier regeneration, the barrier‐improving properties of urea, glycerol, and PEG gels would readily be explained.…”
Section: Commentsupporting
confidence: 79%
See 1 more Smart Citation
“…The present study has confirmed that Polyethylenglykolsalbe DAB hydrates the skin (8), as well as demonstrating that, like glycerol and urea (1–7), it improves stratum corneum barrier function.The present study cannot resolve the controversial issue of the relationship between TEWL and barrier regeneration (1, 3). However, if TEWL does control barrier regeneration, the barrier‐improving properties of urea, glycerol, and PEG gels would readily be explained.…”
Section: Commentsupporting
confidence: 79%
“…Polyethylene glycols (PEGs) are also hygroscopic (7). The PEG ointment Polyethylenglykolsalbe DAB has been shown to hydrate (8). Does it also have a regenerative protective effect?…”
mentioning
confidence: 99%
“…Zinc oil and the moisturizer-free shake emulsion did not show any effect; PEG ointment had a significant hydrating effect [37].…”
Section: Effects Of the Lipids Contained In Emulsion Bases And Of Othmentioning
confidence: 85%
“…1) Η αυξημένη υγρασία στην κερατοειδή στιβάδα, μπορεί να επιτευχθεί με τη χρήση ενυδατικών (όπως αλλαντοϊνη, γλυκερόλη, γαλακτικά οξέα, προπυλικό οξύ, ουρία). Η χρήση των εφυγραντικών ουσιών όπως είναι η ουρία και η γλυκερόλη, προτείνονται ειδικά για τους χρόνιους ατοπικούς ασθενείς, μιας και συντελούν στην αναγέννηση της λειτουργίας του δερματικού φραγμού (179)(180). Στα παιδιά η ουρία θα πρέπει να χρησιμοποιείται σε συγκεντρώσεις που δε είναι υψηλότερες από 3 %, ώστε να αποφευχθούν οι συχνά αναφερόμενοι ερεθισμοί του δέρματος.…”
Section: άλλα νοσήματα μη αλλεργική αιτιολογίας που συνηπάρχουν με ατοπική δερματίτιδαunclassified
“…Για το λόγο αυτό τα σκευάσματα που περιέχουν κορτικοστεροειδή θα πρέπει να εναποτίθενται μόνο στις πάσχουσες περιοχές. Επιπλέον τα διάφορα σκευάσματα που περιέχουν σαλικυλικό οξύ, μεθυλοσαλικινολινικό χλωρίδιο, κλιοκινόλη και ρεσορκινόλη θα πρέπει να αποφεύγονται σε βρέφη και μικρά παιδιά, λόγω των εν δυνάμει παρενεργειών τους (179).…”
Section: άλλα νοσήματα μη αλλεργική αιτιολογίας που συνηπάρχουν με ατοπική δερματίτιδαunclassified